2008
DOI: 10.1111/j.1467-8667.2007.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Response and Modeling of Cantilever Retaining Walls Subjected to Seismic Motions

Abstract: A series of nonlinear, explicit finite difference analyses were performed to determine the dynamic response of a cantilever retaining wall subjected to earthquake motions. This article outlines the calibration and validation of the numerical model used in the analyses and comparisons are presented between the results from the finite difference analyses and results from simplified techniques for computing dynamic earth pressures and permanent wall displacement (i.e., Mononobe-Okabe and Newmark sliding block met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 15 publications
3
13
1
1
Order By: Relevance
“…On the other hand, at yielding acceleration of the system, earth pressure on the stem is minimum. This is in agreement with the findings of other recent experimental and numerical studies [16,17]. Comparing Configurations 1 and 3, it can be clearly identified that rotational modes induce lower earth pressure on the wall, but different distribution leading to a higher point of application of the thrust.…”
Section: Resultssupporting
confidence: 81%
“…On the other hand, at yielding acceleration of the system, earth pressure on the stem is minimum. This is in agreement with the findings of other recent experimental and numerical studies [16,17]. Comparing Configurations 1 and 3, it can be clearly identified that rotational modes induce lower earth pressure on the wall, but different distribution leading to a higher point of application of the thrust.…”
Section: Resultssupporting
confidence: 81%
“…Note that the critical acceleration always increases as the wall toe penetrates the underlying soil layer, thus resulting to an increase in sliding resistance. This has also been observed in numerical simulations [52]. On the other hand, Configuration No3 starts to rotate at initiation of yielding, without any evidence of sliding discontinuities on the recorded accelerations.…”
Section: Experimental Results For Displacements Seismic Loads and Famentioning
confidence: 50%
“…Likewise, kinematic solutions [9] and methods based on the theory of elasticity have been developed [10][11][12][13][14], but their applicability is limited since a small wall deflection can induce a failure state in the soil. Finite elements or finite differences models have been used extensively to analyze retaining structures [15][16][17][18][19][20]. While these methods have been validated against real case histories and experimental data, their predictive capabilities is still debatable.…”
Section: Introductionmentioning
confidence: 99%